Incentive effects of unemployment insurance savings accounts: evidence from Chile - Gonzalo Reyes Hartley; Jan C. van Ours; Milan Vodopivec (Institute for the Study of Labor (IZA), 2010)
This study examines the determinants of job-finding rates of unemployment benefit recipients under the Chilean program. This is a unique, innovative program that combines social insurance through a solidarity fund (SF) with self-insurance in the form of unemployment insurance savings accounts (UISAs) - so as to mitigate the moral hazard problem of traditional unemployment insurance programs. Our study is the first one to empirically investigate whether UISAs improve work incentives. We find that for beneficiaries using the SF, the pattern of job finding rates over the duration of unemployment is consistent with moral hazard effects, while for beneficiaries relying on UISAs, the pattern is free of such effects. We also find that for benefit recipient not entitled to use the SF, the amount of accumulation on the UISA does not affect the exit rate from unemployment, suggesting that such individuals internalize the costs of unemployment benefits. Our results provide strong support to the idea that UISAs can improve work incentives.
Keywords: C41; H55; J64; J65; 330; Unemployment insurance; unemployment duration; savings accounts; Arbeitslosenversicherung; Arbeitslosigkeit; Dauer; Berufliche Integration; Beschäftigungseffekt; Chile